Characteristics of Heart Failure Patients With or Without Hypotension When Transitioning From Nitroprusside to Sacubitril-Valsartan. Issue 3 (September 2021) - Adie, Sarah K.; Ketcham, Scott W.; Abdul-Aziz, Ahmad A.; Thomas, Michael P.; Konerman, Matthew C.
Abstract : Background: Sacubitril-valsartan is an angiotensin receptor–neprilysin inhibitor indicated for the treatment of patients with symptomatic heart failure with reduced ejection fraction (HFrEF). Little is known about outcomes of HFrEF patients transitioned from sodium nitroprusside (SNP) to sacubitril-valsartan during an admission for acute decompensated heart failure. We sought to describe characteristics of patients initiated on sacubitril-valsartan while receiving SNP and, in particular, those patients who did and did not experience hypotension requiring interruption or discontinuation of sacubitril-valsartan. Methods: We performed a retrospective case series of adult patients (>18 years) with HFrEF (left ventricular ejection fraction ⩽40%) admitted to the University of Michigan cardiac intensive care unit between July 2018 to September 2020 who received sacubitril-valsartan while on SNP. Results: A total of 15 patients with acute decompensated heart failure were initiated on sacubitril-valsartan while on SNP. The mean age was 57 ± 15.9 years. Seven (46.7%) patients experienced hypotension. The patients in the cohort who experienced hypotension were numerically older (60 ± 17 vs. 55 ± 15.5), and the majority were white (86%). Patients with hypotension had a numerically lower left ventricular ejection fraction (13 ± 4.2 vs. 18 ± 8.2) and higher serum creatinine (1.4 ± 0.54 vs. 0.88 ± 0.25). Seven (100%) patients received a diuretic on the day of sacubitril-valsartan initiation in those who experienced hypotension compared with 2 (25%) in those who did not experience hypotension. Conclusions: In almost half of patients admitted to the cardiac intensive care unit with acutely decompensated HFrEF, significant hypotension was seen when initiating sacubitril-valsartan while on SNP. Future studies should evaluate appropriate patients for this transition and delineate appropriate titration parameters.